Learning Achievement: Trial of Role Playing Methods for Active and Innovative Students - Nabila Tusysyahidah; Dede Rika; Sela Uswatun Hasanah; Fani Nur Anggraeni; Imam Tabroni (IHSA Institute, 2023)
This research aims to increase achievement study student use role playing method on eye SK I lessons at Miftahul Ulum for the 2022/2023 academic year. The population in this study were all MTs students. Miftahul ulum for the 2022/2023 Academic Year, taking class VII as the sample. Research in this case was also carried out through group and experimental designs. Treatment was given only to subjects in the experimental group within a certain period of time, after which the learning outcomes of the two groups were measured. The average difference between the pre-test and post-test for each group is calculated, then the score of this average difference is compared to ascertain whether the experimental treatment given to the experimental group has caused a greater change in the control group. The data analysis used is t-test or t-statistic. The t-statistical analysis technique devoted to differences in two separate populations. The data normality test technique is intended to test whether the scores in the changes studied have approached the normal distribution or not. Furthermore, the data that has been processed can be concluded. The results obtained are that in the teaching and learning process by using the role playing strategy students have played an active role, have good enthusiasm and get good achievements. Furthermore, in terms of the ability of educators to implement role-playing strategies in the learning process, where from the results of observations made, many important things are often forgotten by educators in implementing role-playing strategies so that they do not function actively, namely educators pay less attention to the purpose of using role-playing when the learning process in the classroom takes place. The consequences are: students sometimes pay less attention to messages conveyed by educators and students often ignore educators' orders.